Prenatal diagnosis of beta thalassaemia by oligonucleotide analysis in Mediterranean populations. Issue 11 (November 1988) - Rosatelli, M C; Tuveri, T; Scalas, M T; Di Tucci, A; Leoni, G B; Furbetta, M; Monni, G; Cao, A
Abstract : We have used four oligonucleotide probes and two restriction enzymes to detect the beta thalassaemia mutation in a group of 61 couples of Italian descent who were prospective parents. We have been able to define the beta thalassaemia mutation in both parents in 47 couples and in only one parent in 12 couples. Prenatal diagnosis was accomplished successfully either by amniocyte (two) or trophoblast (26) DNA analysis in 28 couples in which the pregnancy was in progress. These results indicate that direct identification of the mutation by oligonucleotide or restriction endonuclease analysis is a practical and useful method for prenatal diagnosis of beta thalassaemia in childless couples.